PERAN KPPU DALAM MELINDUNGI KONSUMEN DARI PELAKU USAHA TIDAK SEHAT - Nofita Ariyanti; Widhi Cahyo Nugroho (Gapenas Publisher, 2023)
The KPPU was established in 2000 based on the Prohibition of Monopolistic Practices and Unfair Trade Competition No. 5 of 1999. The background to the creation of the KPPU is the desire to protect consumers from predatory pricing and other forms of market abuse as well as stimulating a dynamic and competitive market. In exercising its functions, the KPPU has the power to monitor compliance with the prohibition of unsound business practices regulated by Law no. 5 of 1999. In its own review of allegations of monopolistic behavior and anti-competitive tactics, the KPPU only requests a report. This survey has been prepared to monitor activities that violate the Unethical Business Practices Act No. 5 of 1999. Whether the complaint comes from the KPPU or from the general public, all are investigated. The purpose of this study is to determine the function of KPPU in protecting consumers against predatory pricing. Using regulatory and conceptual approaches, as well as normative legal research methods, this study examines how the KPPU protects consumers from unfair pricing. The results of the investigation show that the KPPU is empowered to examine corporate figures suspected of carrying out a monopoly strategy